Secular Criticism in the Teaching of Literature: A Bridge to Connect the Letters with Human Experiences, Social Realities and Institutions of Power - Esteban Barboza-Núñez (Revista Electrónica Educare)
Abstract. Based on the contribution of Palestinian literary critic and thinker Said (1983), who coined the term “secular criticism,” this article analyzes the possibility of applying this concept to the process of teaching literature at elementary, secondary and college levels. We should understand secular criticism as the mode of textual analysis that sees literature inherently linked to human experiences, social realities in which it is produced and to the institutions of power that consent or suppress it. The main proposal of the article will be to suggest a methodology to approach literary texts in the classroom from a mundane perspective; that is, linking them to the outside world. In this sense, and using primary literary sources as examples, as well as literary theory, the article will propose turning the study of literature into a tool to analyze, question and challenge the realities that produce it.